Changes in bone structure and the muscle-bone unit in children with chronic kidney disease - Tsampalieros, Anne (2012)
The impact of pediatric chronic kidney disease (CKD) on acquisition of volumetric bone mineral density (BMD) and cortical dimensions is lacking. To address this issue we obtained tibia quantitative computed tomography scans from 103 patients age 5-21 years with CKD (26 on dialysis) at baseline and 12 months later. Gender, ethnicity, tibia length and/or age-specific Z-scores were generated for trabecular and cortical BMD, cortical area, periosteal and endosteal circumference, and muscle area based on over 700 reference subjects. Muscle area, cortical area, and periosteal and endosteal Z-scores were significantly lower at baseline compared to the reference cohort. Cortical BMD, cortical area and periosteal Z-scores all exhibited a significant further decrease over 12 months. Higher parathyroid hormone levels were associated with significantly greater increases in trabecular BMD and decreases in cortical BMD in younger patients (significant interaction terms for trabecular BMD and cortical BMD). The estimated GFR was not associated with changes in BMD Z-scores independent of parathyroid hormone. Changes in muscle and cortical area were significantly and positively associated in control subjects but not in CKD patients. Thus, children and adolescents with CKD have progressive cortical bone deficits related to secondary hyperparathyroidism and potential impairment of the functional muscle-bone unit. Interventions are needed to enhance bone accrual in childhood-onset CKD.